Activation of Orexin System Stimulates CaMKII Expression - Fan, Yuanyuan; Jiang, Enshe; Gao, Huanjia; Bigalke, Jeremy; Chen, Bojun; Yu, Chunxiu; Chen, Qinghui; Shan, Zhiying (Frontiers in Physiology, 2021)
Hyperactivity of the orexin system within the paraventricular nucleus (PVN) has been shown to contribute to increased sympathetic nerve activity (SNA) and blood pressure (BP) in rodent animals. However, the underlying molecular mechanisms remain unclear. Here, we test the hypothesis that orexin system activation stimulates calcium/calmodulin-dependent kinase II (CaMKII) expression and activation, and stimulation of CaMKII expressing PVN neurons increases SNA and BP. Real-time PCR and/or western blot were carried out to test the effect of orexin-A administration on CaMKII expression in the PVN of normal Sprague Dawley (SD) rats and orexin receptor 1 (OX1R) expressing PC12 cells. Immunostaining was performed to assess OX1R cellular localization in the PVN of SD rats as well as orexin-A treatment on CaMKII activation in cultured hypothalamic neurons. In vivo sympathetic nerve recordings were employed to test the impact of optogenetic stimulation of CaMKII-expressing PVN neurons on the renal SNA (RSNA) and BP. The results showed that intracerebroventricular injection of orexin-A into the SD rat increases mRNA expression of CaMKII subunits in the PVN. In addition, Orexin-A treatment increases CaMKII expression and its phosphorylation in OX1R-expressing PC12 cells. Furthermore, Orexin-A treatment increases CaMKII activation in cultured hypothalamic neurons from neonatal SD rats. Finally, optogenetic excitation of PVN CaMKII-expressing neurons results in robust increases in RSNA and BP in SD rats. Our results suggest that increased orexin system activity activates CaMKII expression in cardiovascular relevant regions, and this may be relevant to the downstream cardiovascular effects of CaMKII.